SOIL ERODIBILITY AND ITS EROSION POTENTIAL IN SADAWARNA DAN AND SURROUNDING AREA, CIBOGO DISTRICT, SUBANG REGENCY, WEST JAVA PROVINCE - Alpionisa, Salsabila Nur; Zakaria, Zufialdi; Khoirullah, Nur; Sophian, Raden Irvan; Firmansyah, Yusi (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
The Sadawarna Dam and its surroundings, which are located in Subang Regency, are currently under construction. Change in land use caused by the construction occurred. Land management and soil conservation are needed to prevent uncontrolled erosion because it can caused slopes in critical condition, flood occurred in the downstream areas of river, and silting of dam. One of the information in land management and soil conservation is by identifying the soil erodibility which aims to find out the sensitivity of the soil to erosion in the research area. Soil erodibility affected by grain size distribution, soil structure, soil organic matter, and soil permeability. In this research area, the soil erodibility was calculated based on disturbed sample in the field which was then tested in the laboratory. The laboratory tests include sieve analysis, hydrometer analysis, and %c organic. Soil permeability obtained from previous studies. The research area is dominated by clay-sized soil which are the result of weathered claystone in Subang Formation. Soil erodibility value in the research area ranged from 1,100 – 0,448 t ha h/ha MJ cm with dominance of low soil erodibility classes. The dominance of clay-sized soil causes low soil erodibility value because clay sized soil has cohesive properties so it tends to be difficult to erode.